The Evolution of Corporate Sustainable Performance and Firm Value Research: A Bibliometric Analysis - Frandy Walean; Deske W. Mandagi (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: Research examining the relationship between Corporate Sustainable Performance (CSP) and Firm Value has expanded substantially over the past three decades, creating a diverse and increasingly fragmented body of knowledge. Despite this growth, there is a limited understanding of the intellectual structure, conceptual evolution, and emerging research directions that characterize the field. Research Method: This study employed bibliometric and science mapping analyses of 558 peer-reviewed journal articles indexed in Scopus between 1994 and 2025. Using Bibliometrix and VOSviewer, the study examines publication trends, influential contributors, knowledge structures, and thematic evolution within the literature. Results and Discussion: The findings reveal a significant acceleration in publication and citation activity, particularly after 2020, indicating the field's growing maturity and scholarly influence. China emerged as the leading contributor, while Business Strategy and the Environment was identified as the most influential journal. Science mapping results show that the literature has evolved through five major stages: CSR and sustainability foundations; environmental performance and strategic sustainability; ESG and governance integration; stakeholder value creation; and sustainability branding and symbolic value outcomes. Implications: This progression demonstrates a conceptual shift from viewing sustainability as a responsibility-oriented practice toward recognizing it as a strategic mechanism for value creation, competitive advantage, and organizational resilience. Originality: This study provides a comprehensive overview of the evolution of CSP and Firm Value research and identifies emerging directions that can guide future scholarly development in this rapidly expanding field.